Anti‐vascular endothelial growth factor for prevention of postoperative vitreous cavity haemorrhage after vitrectomy for proliferative diabetic retinopathy - Jonathan M Smith; David HW Steel (Cochrane Database of Systematic Reviews, 2011)
BACKGROUND: Postoperative vitreous cavity haemorrhage (POVCH) is a significant complication following vitrectomy for proliferative diabetic retinopathy (PDR). It delays visual recovery and can make further treatment difficult if the view of the fundus is significantly obscured. A number of interventions to reduce the incidence of POVCH have been proposed, including the perioperative use of anti-vascular endothelial growth factor (anti-VEGF). Anti-VEGFs reduce vascular proliferation and the vascularity of neovascular tissue, which is often the source of bleeding following vitrectomy. OBJECTIVES: The review aims to assess the effect of perioperative anti-VEGF in reducing the incidence of POVCH. SEARCH METHODS: We searched CENTRAL (which contains the Cochrane Eyes and Vision Group Trials Register) (The Cochrane Library 2011, Issue 2), MEDLINE (January 1950 to March 2011), PubMed (10 March 2011), EMBASE (January 1980 to March 2011), Latin American and Caribbean Health Sciences Literature Database (LILACS) (January 1982 to March 2011), the metaRegister of Controlled Trials (mRCT) (www.controlled-trials.com) and ClinicalTrials.gov (www.clinicaltrial.gov). There were no date or language restrictions in the electronic searches for trials. The electronic databases were last searched on 10 March 2011. SELECTION CRITERIA: We included all randomised controlled trials (RCTs) that looked at the use of anti-VEGFs and the incidence of POVCH in people undergoing vitrectomy for PDR. DATA COLLECTION AND ANALYSIS: Both review authors independently assessed and extracted the data using a standardised form based on the CONSORT statement. MAIN RESULTS: We included four studies (202 eyes of 198 participants) in this review. The four RCTs met the inclusion criteria, but we were unable to conduct a meta-analysis due to methodological issues in three of the trials. We have provided a summary of the effects of the interventions. We have also provided a summary of the current literature addressing each primary and secondary outcome. AUTHORS' CONCLUSIONS: Results from one of the included studies support the use of preoperative intravitreal bevacizumab to reduce the incidence of early POVCH. There are currently no other high quality RCTs that support the use of anti-VEGF agents perioperatively to reduce the incidence of early or late POVCH. The remaining studies identified by the search suggest that the preoperative use of bevacizumab may reduce the incidence of early POVCH, but it should be recognised that there are a number of significant methodological issues in these studies that lead us to be cautious when interpreting their findings and make any definitive conclusions unwarranted.